REMOTE RADAR CONTROL OF RADIOACTIVE EMISSIONS TO ATMOSPHERE - V. I. Veremjev; O. A. Markelov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An overview of scientific research in the field of methods for radioactive atmosphere heterogeneities with anthropogenic origin radar monitoring is given bellow. The results of analysis of the complex physic-mathematical model of electromagnetic waves scattering from ionized formations in atmospheric surface layers are presented. The directions for future research in improvement of electromagnetic wave interaction with radioactive meteorological formations model are shown.